Synthesis of hyperbranched polyurethane sizing agent with high-solid content via self-catalytic method for improving interfacial adhesion of CF/PA6 composites. (29th September 2022) - Gao, Longxuan; Yan, Fei; Dai, Shengtao; Zhao, Lianshuang; Wang, Junming; Liu, Yu; Ao, Yuhui; Liu, Liu
Abstract: To improve the unsatisfactory interfacial adhesion of carbon fiber/polyamide-6 (CF/PA6) composites, a hyperbranched waterborne polyurethane (HWPU) sizing agent with high-solid content was designed. As a carboxy chain extender for HWPU, carbic anhydride-tris(hydroxymethyl)methyl aminomethane (CA-THAM) with a self-catalytic capacity was synthesized to accelerate the chain extension. The synthesized hyperbranched polyurethane exhibited low viscosity, along with a strong double-electron layer conformation after dispersing in water. The electrostatic repulsion between the latex particles effectively prevented agglomeration, delivering a high solid content of 58% for the sizing agent. The influence of different sizing agent concentrations on the wettability of CF as well as the interfacial properties of composites was systematically studied. Compared with unsized CF/PA6 composites, the interlaminar shear strength and flexural strength of CF-1.5 wt%/PA6 composites were up to 60.3 MPa and 508.4 MPa, with an increment of 50.3% and 27.7%, respectively. Furthermore, the interfacial strengthening mechanism of sizing agent was discussed. The preparation of this high-solid content sizing agents was facile and environmentally friendly, which would hopefully reduce costs during the transportation. Graphical abstract: Schematic diagram of strengthening mechanism in HWPU-sized CF/PA6 composites. Image 1 Highlights: The chain extender with self-catalyst property was synthesized. The solid content of hyperbranched polyurethane sizing agent can be arrived at 58%. An inexpensive and natural castor oil was used to replace petroleum-based polyol. The interfacial adhesion of modified composites was effectively strengthened.